Introduction to philosophy: Ethics - Matthews, George (Rebus Community, 2019)
We often make judgments about good and bad, right and wrong. Philosophical ethics is the critical examination of these and other concepts central to how we evaluate our own and each others' behavior and choices. This text examines some of the main threads of discussion on these topics that have developed over the last couple of millenia, mostly within the Western cultural tradition. It considers basic questions about moral and ethical judgment: Is there such a thing as something that is really right or really wrong independent of time, place and perspective? What is the relationship between religion and ethics? How can we reconcile self-interest and ethics? Is it ever acceptable to harm one person in order to help others? What do recent discussions in evolutionary biology or have to say about human moral systems? What is the relation between gender and ethics? The authors invite you to participate in their exploration of these and many other questions in philosophical ethics
Keywords: Philosophy / Textbooks; Philosophy; Electronic books; Textbooks